PENGARUH BAHAN AJAR ICT MENGINTEGRASIKAN MSTBK MATERI GERAK HARMONIS, MOMENTUM, DAN IMPULS TERHADAP KOMPETENSI FISIKA SISWA KELAS XI SMAN 1 LUBUK ALUNG - Aulia Fitri; Asrizal Asrizal; Harman Amir (PILLAR OF PHYSICS EDUCATION, 2015)
Globalization era requires high quality of human resources. Improvement the human resources can be done through education process. Reality shows that physics learning in high school is not optimal yet, that competency of student is low. Alternative solution to solve this problem is ICT learning materials by  integrating Mathematics, Science, Technology, Natural disaster, and Character values (MSTDC). The purposes of this research are to determine the student’s Physics competency and to investigate the effect of applying ICT learning materials toward the student’s Physics competency at grade XI in SMAN 1 Lubuk Alung. Type of this research is Quasi Experimental with Randomized Control Group Only Design. The research population are students of grade XI Science SMAN 1 Lubuk Alung who listed in the  2014/2015 academic year. Sampling technique which is used in this research is purposive sampling. Data analysis techniques are descriptive statistic and compare mean of knowledge, attitude, and skill of students. Based on data analysis can be stated  two results of this research. First, average value of student who use ICT learning materials by integrating MSTDC in the competency of knowledge, attitude, and skill respectively are 86.03; 90.10; and 90.84. Second, implementation ICT learning materials by integrating MSTDC gives significant effect toward student's Physics competency including knowledge, attitude, and skill at 0,05 signification level